Development of stained polymeric nanocapsules loaded with model drugs: Use of a fluorescent poly(phenyleneethynylene) - Campos, Estefania V. R. [UNESP]; Oliveira, Jhones L. [UNESP]; Zavala-Betancourt, Sara A.; Ledezma, Antonio S.; Arias, Eduardo; Moggio, Ivana; Romero, Jorge; Fraceto, Leonardo F. [UNESP] (Elsevier B.V., 2016)
A phenyleneethynylene polymer (here denoted pPy3E-sqS) was synthesized and characterized by UV-vis spectroscopy, fluorescence spectroscopy, and TEM, and was used for the staining of polymeric nanocapsules. The nanocapsules presented good temporal stability, without changes in shape or fluorescence, and were suitable for use in drug release systems. The mean particle size was around 430 nm, the polydispersity index was below 0.2, and the zeta potential was around -13 mV. The release kinetics is one of the most important factors to consider in drug delivery systems, and here it was observed that nanocapsules containing the fluorescent polymer still maintained the ability to modulate the release of the fungicides tebuconazole and carbendazim (used as model drugs) after 4 days. Preliminary results indicated that staining with the fluorescent pPy3E-sqS polymer could be used as a valuable tool to track the behavior of polymeric systems in the environment. However, further studies will be needed to clarify the environmental behavior and possible toxicity. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Stained nanocapsules; Fluorescent polymer; Polymeric nanocapsules; Environmental applications; Phenyleneethynylene polymer